2011
DOI: 10.1097/mco.0b013e32834bfe94
|View full text |Cite
|
Sign up to set email alerts
|

Curcuma as a functional food in the control of cancer and inflammation

Abstract: Various in-vitro and in-vivo and scarce number of clinical studies on curcumin were identified. The various effects and properties of curcumin are summarized in this review, including preclinical and especially clinical studies. This review concentrates on recent knowledge and research with curcumin clinical applications, and clinical studies, focusing on studies published between 2008 and 2011 demonstrating the gap between preclinical and clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 51 publications
0
59
0
Order By: Relevance
“…Curcumin also has anti-cancer effect at various stages such as tumor initiation, promotion, and progression in different types of cancers (Surh and Chun 2007). Several clinical trials with curcumin have shown positive effect on cancer prevention (Schaffer et al 2011). Curcumin also appeared to possess pharmacological activity to slow down the aging process and extend lifespan of Drosophila (Salvioli et al 2007;Sikora et al 2010;Suckow and Suckow 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin also has anti-cancer effect at various stages such as tumor initiation, promotion, and progression in different types of cancers (Surh and Chun 2007). Several clinical trials with curcumin have shown positive effect on cancer prevention (Schaffer et al 2011). Curcumin also appeared to possess pharmacological activity to slow down the aging process and extend lifespan of Drosophila (Salvioli et al 2007;Sikora et al 2010;Suckow and Suckow 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin (diferuloylmethane) is polyphenolic compound derived from spices turmeric, a product of the plant curcuma longa [5]. The pigments responsible for yellow color of curcumin are phenolic in nature and are known by the name curcuminoids, which occur naturally in curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, the principal polyphenolic cucuminoid, extracted from the turmeric rhizome Curcuma longa Linn, has been vastly reported for its biological activities, including anti-inflammatory (Schaffer et al, 2011), anti-oxidant (Speciale et al, 2011), anti-infection (Na et al, 2011) and anti-cancer (Bansal et al, 2011). Moreover, curcumin can cross the blood-brain barrier and is neuroprotective in neurological disorders (Song et al, 2012).…”
Section: Introductionmentioning
confidence: 99%